Skill Level, Bottom Passing and Upper Passing in Volleyball, Extracurricular Participants of Junior High School 3 Banjarbaru - Navia Paramita; Mita Erliana; Norma Anggara (Universitas Negeri Semarang, 2024)
The aim of this research is to determine the level of lower passing and upper passing skills of extracurricular participants at Junior High School 3 Banjarbaru. This research method is descriptive quantitative with tests measuring the lower passing and upper passing skills of volleyball in extracurricular participants at Junior High School 3 Banjarbaru. The results of research on men’s underpassing were classified as very good 20%, good classification 20%, moderate 20%, poor 30%, very poor 10%, research results on female underpassing were classified as very poor 100%. The results of the passing research on boys were classified as very good 20%, good 20%, moderate 20%, poor 30%, very poor 10%, the results of the research on passing on girls were classified as very less than 100%. The conclusion of the research results is that the lower passing of the sons of extracurricular participants at Junior High School 3 Banjarbaru is poor, and the girls’ passing is very poor. The conclusion of the research results is that the passing of the sons of extracurricular participants at Junior High School 3 Banjarbaru is poor, and the daughters are very poor.